Glycine nanostructures and domains in beta-glycine: computational modeling and PFM observations - Bystrov, V. S.
In this work computational molecular modeling of -glycine nanostructures is presented, using various approaches, mostly semi-empirical quantum approximation PM3 type in HyperChem software in restricted Hartree-Fock calculations. The main aims of present studies focus on the molecular modeling for the -glycine domains and domain walls formation and interaction. Obtained results are presented in visual 3D-models of the glycine domains and domain walls, compared with experimentally observed by PFM domain walls structures. Modeling is arranged with calculated values of physical data (polarization, etc.). Analysis of these new computed and corroborated PFM experimental data for -glycine domains are presented.